PRIORITY BASED AUTOMATIC MULTI SOURCE SWITCHING USING PLC (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The main purpose of this project is to provide continuous power supply to the load by switching the supply. In case if anyone of the source is absent from the following four sources namely solar, inverter, mains and generator. Automatically other three provides backup & shares the load .The graph of need of electric supply is growing day by day and the frequent power disconnection of electricity are causing many issues in different areas like banks, colleges schools, hospitals, houses and industries. Thus there is requirement of Energy source for an alternate arrangement of power supply. In this project arrangement has been designed by using Allen Bradely PLC and relays. When a source, say mains fails the power supply to the load then automatically it shifts to next priority source generator and so on. LEDs are used to indication purpose for running source which is used to provide the supply.